Control of pervasive domestic-scale inverters for minimizing total feeder power - Deakin, M; Morstyn, T; McCulloch, M (Elsevier, 2020)
This paper proposes a method for studying the potential benefits of reactive power control by domestic-scale inverters, considering network losses, inverter losses, and load-voltage sensitivity. The model is developed as a mixed-integer quadratically constrained quadratic program (MI-QCQP), using a linearization of the unbalanced distribution load flow equations. Networks both with and without on-load tap changers are studied, with the test cases covering both European and North American-style circuits. The use of domestic inverter control is shown to increase benefits compared to conventional tap control by 20%, reducing the total feeder power draw by as much as 0.5% of the feeder load. In contrast, the minimization of either load or losses in isolation is shown to increase the amount of power that a feeder draws in five of the seven circuits. To reduce the communications overhead of the approach, a control scheme is proposed that specifies the reactive power of all inverters on each phase identically; this approach is shown to realise up to 98% of the potential benefits of inverter reactive power control.